Le Roman de Fauvel - Schrade, Leo; Roesner, Edward H. (Monaco Éditions de l'Oiseau-Lyre, 1984)
Reprint of 34 polyphonic works, in Latin and French, first published in: The roman de Fauvel. . (Polyphonic music of the fourteenth century ; 1)
Keywords: Middle Ages (500-1400); Novel; Satire; Politics; France